A structure–activity relationship study of the positive allosteric modulator LY2033298 at the M4 muscarinic acetylcholine receptor. Issue 11 (8th October 2015) - Szabo, Monika; Huynh, Tracey; Valant, Celine; Lane, J. Robert; Sexton, Patrick M.; Christopoulos, Arthur; Capuano, Ben
Abstract : Positive allosteric modulators targeting the M4 muscarinic acetylcholine receptor offer greater sub-type selectivity and unique potential as CNS agents through their novel mode of action to traditional orthosteric ligands. Abstract : Positive allosteric modulators (PAMs) targeting the M4 muscarinic acetylcholine receptor (mAChR) offer greater sub-type selectivity and unique potential as central nervous system agents through their novel mode of action to traditional orthosteric ligands. In an attempt to elucidate the molecular determinants of allostery mediated by the exemplar thienopyridine M4 mAChR PAM, LY2033298, we report herein a systematic structure–activity relationship (SAR) study investigating different linkage points, halogen replacements to examine size and electronic effects, and different substitution combinations on the thienopyridine scaffold. We applied an operational model of allosterism to determine values of functional affinity ( K B ), cooperativity ( αβ ) and intrinsic agonism ( τ B ) for all compounds.